EVALUATION OF ANTIMICROBIAL, CYTOTOXICITY, AND DYEING PROPERTIES OF PRODIGIOSIN PRODUCED BY SERRATIA MARCESCENS STRAIN JAR8 - Chauhan, Ritika; Choudhuri, Aniket; Abraham, Jayanthi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: Prodigiosin is a red tripyrrole pigment which is synthesized as a secondary metabolite by biotypes A1, A2, and A6 of Serretia marcescens. This study was aimed to optimize production parameters for prodigiosin pigment produced by S. marcescens strain JAR8 and to determine its antimicrobial, cytotoxicity, and dyeing properties. Methods: The effect of various media components, process parameters (temperature, pH, incubation period), and other supplements was investigated, and the maximum production of prodigiosin was found to be at temperature 28Â°C, pH 7.0, incubation period of 5 day with peptone in the media. Antibacterial, cytotoxicity, and dyeing properties of prodigiosin were studied in depth. Results: The antimicrobial study of prodigiosin revealed that it is a potent inhibitor of Gram-positive bacteria as well as Gram-negative bacteria. The prodigiosin exhibited commendable dose-dependent cytotoxicity effect against human bone cancer cells with the IC50 of 108 Î¼g/ml. Prodigiosin produced by strain JAR8 resisted the action of acid, alkali and detergent when applied to textile cloth. Conclusion: The deep red pigment prodigiosin produced by strain JAR8 is economically effective and can be categorized as microbial natural product for further pharmaceutical applications.